The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s11042-023-15930-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimized deep learning vision system for human action recognition from drone images

Abstract: There are several benefits to constructing a lightweight vision system that is implemented directly on limited hardware devices. Most deep learning-based computer vision systems, such as YOLO (You Only Look Once), use computationally expensive backbone feature extractor networks, such as ResNet and Inception network. To address the issue of network complexity, researchers created SqueezeNet, an alternative compressed and diminutive network. However, SqueezeNet was trained to recognize 1000 unique objects as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…Over the years, activity within the UAV autonomy research space has led to a steady increase in published research on novel solutions for autonomous navigation features. Many of these projects use trained models to infer a solution to autonomous UAV tasks [1][2][3][4]. Previous reviews of state-of-the-art solutions in the autonomous navigation research space revealed that, of the classified autonomous features, collision avoidance, obstacle detection, and object distinction (including object detection) were the most popular research topics.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, activity within the UAV autonomy research space has led to a steady increase in published research on novel solutions for autonomous navigation features. Many of these projects use trained models to infer a solution to autonomous UAV tasks [1][2][3][4]. Previous reviews of state-of-the-art solutions in the autonomous navigation research space revealed that, of the classified autonomous features, collision avoidance, obstacle detection, and object distinction (including object detection) were the most popular research topics.…”
Section: Introductionmentioning
confidence: 99%